The inter-relationship between initial profits, growth-focused firms and profit-focused firms: Evidence from KSE 100-index Pakistan - Maryam Jabeen; Attaullah Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Profit and growth are considered as important goals in managing firms. This study tests the impact of initial profits on the growth and profit on a sample of firms listed at Karachi Stock Exchange (KSE) for the period 2006 to 2011. In addition to initial profits the study also checked the impact of leverage, firm's size and age on profitable growth. Logistic regression borrowed from the work of Davidsson et al. (2009) was used to find out whether profit at initial stages of the firm determines profitable growth for the firm. The average growth rate of the companies was calculated for the last three years. After calculating the average growth rate the firms were then classified into two groups based on the median value of the growth. High growth firms were further classified into low and high profits based on the median of ROA (Return on Assets). The findings showed that initial profits had a positive significant impact on profitable growth. While firm's size, age and leverage had no impact on profitable growth of the sampled firms. In comparison to growth-focused firms, profit-focused firms are more likely to reach a state of high growth and high profits.
Keywords: 330; firm growth; initial profit; profitable growth; firm's size; resource-based view; firm's age; leverage